«Prospero players»: recita e metamorfosi dell'io in Salman Rushdie (Mantichora. Italian Journal of Performance Studies, 2020)
This paper explores in depth the microcosm set out by Salman Rushdie, in which the many perfomances of characters configure the bachtinian ‘pluridiscoursiveness’ as a simultaneous presence of multiples, metamorphic, voices.